Formation of columnar mesophases by calamitic molecules: a modulated SmA phase in mixtures of amphiphilic and bolaamphiphilic biphenyl derivatives - SAUER, CHRISTIANE; DIELE, SIEGMAR; TSCHIERSKE, CARSTEN (Liquid crystals, 1997)
Binary mixtures of bolaamphiphilic biphenyl derivatives with each other and with amphiphilic biphenyl derivatives were investigated by means of optical microscopy. The miscibility of the bolaamphiphiles is very sensitive to the molecular length of the components. The SmA phases of bolaamphiphiles with the same length are completely miscible. If the length difference between the two components of the binary system increases, a miscibility gap occurs. Due to their different phase structures (bilayer versus monolayer) no miscibility in the SmA phases was found for amphiphilic and bolaamphiphilic compounds with comparable molecular lengths. However, in some cases a novel mesophase was induced in the contact region. This mesophase was investigated by X-ray diffraction. It represents a two-dimensionally modulated (columnar) phase with a rectangular lattice (Col r), but the local order is similar to that of disordered smectics. Its formation is explained in terms of ribbon structures resulting from the collapse of smectic bilayers, in strong analogy to the antiphases (SmA) of terminally polar calamitic mesogens.